(untitled) (Práxis Educativa, 2024)
In this article, the objective is to understand the republican ideals in Paraná, Brazil, implemented by Cesar Prieto Martinez, which shaped the education reform at the beginning of the 20th century, the fight for the creation of school groups in Paraná, and the strengthening of Normal Schools during his time leading the General Inspectorate of Education. Primary sources used include pedagogical press and printed texts from the magazine “O Ensino” [The Teaching], specifically the issues from 1922, 1923, and 1924, which portrayed the ideals of the General Inspector of Education, Cesar Prieto Martinez, along with the messages of the Presidents of the State of Paraná from the 1920s and the Reports of the General Inspector of Education of Paraná. These documents demonstrate how significant Cesar Prieto Martinez’s presence was in educational management during the 1920s in Paraná, highlighting the struggle for the establishment of the first school groups and the first teacher training school in Ponta Grossa. Keywords: Cesar Prieto Martinez. School groups. Normal School in Paraná.